A Comparison of the Demographic and Clinical Characteristics of Caregivers of Autistic Children and Caregivers of Children with Fetal Alcohol Spectrum Disorder. Issue 2 (3rd April 2022) - Redquest, Brianne; McKenzie, Lachina; Lake, Johanna; Fung, Kenneth; Lunsky, Yona
ABSTRACT: Introduction: Caregivers of autistic children and caregivers of children with fetal alcohol spectrum disorder (FASD) experience considerable stress. However, what is unique or similar across these groups remains understudied. This study explored how female caregivers of children with FASD who registered to participate in a caregiver focused mental health intervention differed from female caregivers of autistic children participating in a similar intervention. Methods: Prior to the intervention, caregivers of children with FASD (n = 21), and caregivers of autistic children (n = 22) were asked to complete an online baseline questionnaire. This questionnaire collected information pertaining to caregiver and child demographics, as well as clinical characteristics related to wellbeing, values, and what caregivers identified as rewarding and challenging about raising their child. Results: Results identified similarities across caregiver groups in terms of wellbeing, values, and the challenges and rewards they identified with raising their children. Conclusions: Given the similarities in these two caregiver groups, and the shortage of research on families of people with FASD relative to families of autistic people, interventions for family caregivers in the autism community may also be applicable for FASD families, for whom fewer resources are available.